2017
DOI: 10.3389/fpls.2017.01591
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Role of CBF/DREB Transcription Factors and Dehydrins in Maintaining the Quality of Table Grapes cv. Autumn Royal Treated with High CO2 Levels and Stored at 0°C

Abstract: C-repeat/dehydration-responsive element binding factors (CBF/DREB) are transcription factors which play a role in improving plant cold stress resistance and recognize the DRE/CRT element in the promoter of a set of cold regulated genes. Dehydrins (DHNs) are proteins that accumulate in plants in response to cold stress, which present, in some cases, CBF/DREB recognition sequences in their promoters and are activated by members of this transcription factor family. The application of a 3-day gaseous treatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 77 publications
2
44
0
Order By: Relevance
“…As a consequence, the incorporation of postharvest technologies that reduce the use of agrochemical compounds is vital to maintain the quality of fruit and vegetables during their storage. The application of a gaseous treatment with 20 kPa CO 2 for 3 days at 0 °C was effective in maintaining the quality of red table grapes during postharvest storage at low temperature by reducing total decay, weight loss, and rachis browning . Although table grapes are classified as chilling tolerant, our previous works have shown that the 3‐day gaseous treatment helped red table grapes to withstand temperature shifts at 0 °C .…”
Section: Introductionsupporting
confidence: 56%
See 4 more Smart Citations
“…As a consequence, the incorporation of postharvest technologies that reduce the use of agrochemical compounds is vital to maintain the quality of fruit and vegetables during their storage. The application of a gaseous treatment with 20 kPa CO 2 for 3 days at 0 °C was effective in maintaining the quality of red table grapes during postharvest storage at low temperature by reducing total decay, weight loss, and rachis browning . Although table grapes are classified as chilling tolerant, our previous works have shown that the 3‐day gaseous treatment helped red table grapes to withstand temperature shifts at 0 °C .…”
Section: Introductionsupporting
confidence: 56%
“…Actin1 (XM_002282480) from V. vinifera was used as internal control. The specificity of products was validated as described by Vazquez‐Hernandez et al …”
Section: Methodsmentioning
confidence: 73%
See 3 more Smart Citations